Forest degradation and biomass changes over forest area in Indonesia's new capital city and surrounding area. Issue 1 (1st November 2022) - Adinugroho, W C; Prasetyo, L B; Kusmana, C; Krisnawati, H
Abstract: Anthropogenic interventions in natural forests have resulted in deforestation and forest degradation. There is a reduction in the number of trees per unit area, which results in changes in forest biomass stocks. Deforestation and forest degradation are believed to contribute to increasing the atmosphere's greenhouse gases. Satellite remote sensing has played an essential role in generating information about deforestation and forest degradation. This study aims to analyze forest degradation and biomass stock changes over forest area in Indonesia's new capital city and surrounding area from 2010 to 2018. Spatial datasets from the Tropical Moist Forests project were used in the analysis and processed using Google Earth Engine. Changes in biomass were analyzed based on a biomass map that was produced using radar data. The results of this study clearly show that in the 2010-2018 period, there have been dynamics of forest cover changes in the new capital city of Indonesia and its surroundings, namely the occurrence of direct deforestation, deforestation after degradation, forest degradation, regrowth, and undisturbed forests. The rate of forest degradation was 34, 216 ha yr -1 from 2010 to 2018. The highest rate of forest degradation occurred in 2015, along with the massive incidence of fires. The average aboveground biomass stock in the primary forest is 268 Mg ha -1, while 238 Mg ha -1 in the secondary forest. The loss of some trees resulted in a decrease forest biomass in 2018 by 6.7% of the forest biomass stock in 2010. Forest degradation events are caused mainly by logging and fires that generally occur in extreme drought conditions.